Theoretical Studies of Femtosecond Photoionization for the $Na_2$ Molecule (Journal of Atomic and Molecular Sciences, 2010)
Multiphoton ionization of the $Na_2$ molecule by a single phase shaped femtosecond laser pulse has been theoretically studied using time-dependent quantum wave packet method including the effect of molecular rotation. We analyze the temporal development of the population and further discuss the molecular motion by mapping the rovibrational wave packet propagation in the excited state. The calculated results show a strong dependence of the kinetic energy-resolved photoelectron spectra on the laser chirp directions and the pulse duration.
Keywords: multiphoton ionization; photoelectron spectra; time-dependent wave packet; effect of rotation.